Laser-excited elastic guided waves reveal the complex mechanics of nanoporous silicon - Marc Thelen (Nature Portfolio, 2021)
Assessing mechanics of nanoporous silicon is challenging, but important for new applications. Here, the authors use non-destructive laser-excited elastic guided waves detected contactless, to study dry and liquid-infused single-crystalline porous silicon, revealing its complex mechanics and significant deviations from bulk silicon.